Expression of the nuclear encoded OEE1 protein is required for oxygen evolution and stability of photosystem II particles in Chlamydomonas reinhardtii. - Mayfield, S P (1987)
In Chlamydomonas reinhardtii the oxygen evolving enhancer protein 1 (OEE1), which is part of the oxygen evolving complex of photosystem II (PS II), is coded for by a single nuclear gene (psb1). The nuclear mutant FuD44 specifically lacks the OEE1 polypeptide and is completely deficient in photosynthetic oxygen evolution. In this mutant a 5 kb DNA insertion into the 5' region of the psb1 gene results in the complete absence of OEE1 mRNA and protein. A revertant, FuD44-R 2, which is capable of 30% of the photosynthetic oxygen evolution of wild-type cells, has lost 4 kb of the 5 kb DNA insert, and accumulates both OEE1 mRNA and protein, although at levels somewhat less than those of wild-type cells. Absence of the OEE1 protein in the FuD44 mutant does not affect the accumulation of other nuclear encoded PS II peripheral polypeptides. OEE1 absence does, however, result in a more rapid turnover of the chloroplast encoded PS II core polypeptides, thus resulting in a substantial deficiency of PS II core polypeptides in FuD44 cells. These PS II core proteins again accumulate in revertant FuD44-R2 cells.